Does Transvaginal Ultrasonography Have Good Diagnostic Value in Endometrial Pathology? - S, Moradan; R, Ghorbani; M, Far (IIUM Medical Journal Malaysia, 2011)
Introduction: Endometrial biopsy is usually considered unnecessary in post-menopausal uterine bleeding when the endometrial thickness (ET) is less than 5 mm because the risk of endometrial hyperplasia or cancer is low. However, there is still much controversy from this as some believe that the diagnostic value of ET in diagnosis of endometrial pathology (EP) in postmenopausal bleeding is necessary. In this study, the diagnostic value of ET for diagnosis of EP in post-menopausal bleeding was evaluated. Materials and methods: Sixty post-menopausal women with uterine bleeding were evaluated. Transvaginal ultrasonography (TVS) was used for measurement of ET followed by dilatation and curettage in a one-day interval. According to the EP, patients were divided in two groups, normal and abnormal. Endometrial atrophy was considered as normal and hyperplasia, polyps and carcinoma was considered as abnormal. Results: Twenty nine cases had ET more than 6 mm, among them, 25 cases had abnormal pathology (hyperplasia, polyp, cancer) and 4 cases were normal (atrophy). Thirty-one patients had ET equal or less than 6mm, among them, 26 cases were normal (atrophy) and 5 cases had abnormal pathology. The sensitivity, specifi ty, positive and negative predictive values of TVS in the diagnosis of uterine pathology were 83.3%, 86.7%, 86.2%, 83.9% respectively. Conclusion: We suggest that an ET of less than 6 mm in TVS is unlikely to indicate EP in post-menopausal women with uterine bleeding.